Love and Its Objects
XII, 243 p.
Keywords: This collection of essays on the philosophy of love, by leading contributors to the discussion, places particular emphasis on the relation between love, its character and appropriateness and the objects towards which it is directed: romantic and erotic partners, persons, ourselves, strangers, non-human animals and art.